IMPROVING COMMUNITY AWARENESS FOR A CLEAN AND HEALTHY LIFE TO PREVENT THE SPREAD OF COVID 19 IN TANAH KALI KEDINDING, KENJERAN, SURABAYA - Alfiah, Taty; Handriyono, Rachmanu Eko; Pramestyawati, Talent Nia (Journal of Community Based Environmental Engineering and Management, 2021)
High population density in urban areas is a challenge in preventing the spread of Covid 19. High population density encourages the occurrence of crowds in public facilities, which has a great potential for the spread of the Covid 19 virus. People's awareness to live clean and healthy is an individual's role in realizing personal health , family and the environment. One of the healthy behaviors is the habit of washing hands with soap, which is an effort to prevent the spread of Covid 19. However, everyone's awareness is different, influenced by their socio-economic background. Education on clean and healthy living needs to be carried out continuously, therefore, ITATS Environmental Engineering Department, conducts community service activities in the form of education on clean and healthy living in Tanah Kali Kedinding Village, Kenjeran, Surabaya.